Perbandingan Hasil Gradasi Nail Art Dengan Menggunakan Teknik Airbrush Dan Nail Polish - Madya Sari; Maspiyah; Nia Kusstianti; Dewi Lutfiati (Jurnal Tata Rias, 2025)
The aim of this research is to compare the results of nail art gradations using airbrush and nail polish. This research uses an experimental approach with quantitative methods to test variables. The independent variables in this research are the airbrush technique and nail polish technique. The targets in this research were 5 lecturers and 25 students. The data collection technique used observation while data analysis used statistical analysis of the t-test with SPSS version 29. The results of the study showed that the level of significance was above 0.05, which means that there was no significant difference in the five aspects tested. The texture aspect produced a value of 0.262, the color gradation aspect obtained a value of 0.096, the design suitability aspect obtained a value of 0.050, the neatness aspect obtained a value of 0.118, and the flatness aspect obtained a value of 0.379. So statistically, there is no significant difference between using the airbrush and nail polish techniques. The conclusion of this study is that both using the airbrush and nail polish techniques have their own advantages and disadvantages that can affect the work process and the final result. The airbrush and nail polish techniques do not show significant differences, so both have equivalent quality and can be used according to needs.